Duration of Parathyroid Function Recovery in Patients With Protracted Hypoparathyroidism After Total Thyroidectomy for Papillary Thyroid Carcinoma - Qiu, Yuxuan; Xing, Zhichao; Xiang, Qiao; Yang, Qianru; Su, Anping; Luo, Yan (Frontiers in Endocrinology, 2021)
Purpose: The aim of the present study is to investigate the time to recovery of parathyroid function in patients with protracted hypoparathyroidism at 1 month after total thyroidectomy of papillary thyroid carcinoma. Materials and Methods: Adult patients who underwent total thyroidectomy for papillary thyroid cancer were included. Cases of long-term hypoparathyroidism were studied for recovery of parathyroid function during the follow-up. The duration of recovery and associated variables were recorded. Results: Out of the 964 patients, 128 (13.28%) developed protracted hypoparathyroidism and of these, 23 (2.39%) developed permanent hypoparathyroidism and 105 (10.89%) recovered: 86 (8.92%) before 6 months, 11 (1.14%) within 6 and 12 months and 8 (0.83%) after 1 year follow-up. Variables significantly associated with the time to parathyroid function recovery were number of autotransplanted parathyroid glands (HR, 1.399; 95% CI, 1.060 – 1.846; P = 0.018), serum calcium concentration >2.07 mmol/L (Hazard ratio [HR], 1.628; 95% confidence interval [CI], 1.009 – 2.628; P = 0.046) and PTH level > 1.2 pmol/L (HR, 1.702; 95% CI, 1.083 – 2.628; P = 0.021) at 1 month postoperatively. Conclusion: Permanent hypoparathyroidism should not be diagnosed easily by time, since up to one-fifth of the patients will experience recovery after a period of 6 months and a few patients even beyond one year. The number of autotransplanted parathyroid glands is positively associated with the time to parathyroid function recovery.